Alcohol and remembering a hypothetical sexual assault: Can people who were under the influence of alcohol during the event provide accurate testimony?. Issue 8 (13th September 2016) - Flowe, Heather D.; Takarangi, Melanie K. T.; Humphries, Joyce E.; Wright, Deborah S.
Abstract : We examined the influence of alcohol on remembering an interactive hypothetical sexual assault scenario in the laboratory using a balanced placebo design. Female participants completed a memory test 24 hours and 4 months later. Participants reported less information (i.e., responded "don't know" more often to questions) if they were under the influence of alcohol during scenario encoding. The accuracy of the information intoxicated participants reported did not differ compared to sober participants, however, suggesting intoxicated participants were effectively monitoring the accuracy of their memory at test. Additionally, peripheral details were remembered less accurately than central details, regardless of the intoxication level; and memory accuracy for peripheral details decreased by a larger amount compared to central details across the retention interval. Finally, participants were more accurate if they were told they were drinking alcohol rather than a placebo. We discuss theoretical implications for alcohol myopia and memory regulation, together with applied implications for interviewing intoxicated witnesses.